The Management of Scout in Student Building Character in SMP N 1 BASO - Kartika Sari; Ahmad Sabandi; Sufyarma Marsidin (Jurnal Aplikasi IPTEK Indonesia, 2018)
This research was based on the fail to buil the student character by scout activity. The purpose of this research is to analyze the management of scout activity in school. It used qualitative approach to analyse the management of scout activity in school.  It used qualitative approach to analyse, to organize, to execute and to supervise the management scout in school. The data collected from headmaster, vice headmaster, scoutmaster and students. Had been doing by obsevation, interview and documentations. It was also analyzed by data reduction technique, data sample and summarizing to determine the exact implementation for character building. The data was examined by triangular technique and source. The research showed that scout management in effort to build student character was done by school by formulating, deciding and developing character values in scout vision, mission, purpose and work plan. Yet it was not determined the duty and right of scout implementer approplated whith the competency so it has not been developing the attitude of sprituality, emotion, social, intelectuality and phisic of student. It happened because the headmaster had not executed the supervision and monitory, report and follow-up the work plan. It is excepted to all school element to cooperate in doing scout management to build scout character in student.